2008
DOI: 10.1007/s00268-008-9859-3
|View full text |Cite
|
Sign up to set email alerts
|

Do Tumor Cavitation and Sex in Resected Stage I Non‐Small‐Cell Lung Cancer Correlate with Prognosis?

Abstract: Tumor cavitation, pathologic stage IB, and being male are predictors of poor outcome for patients with stage I NSCLC who undergo resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Hsu et al 78) reported that median survival was the same for never-smoking women and never-smoking men with adenocarcinoma, suggesting that both smoking status and histologic type rather than gender decided survival. In several studies, 34,40,70) a significant survival advantage for women disappeared after statistically adjusting for smoking status, although in other studies 28,41,49,51,53,57,58,76,77) survival advantages for women persisted after adjustment for smoking. In our meta-analysis, which combined these conflicting studies, female gender still persisted as a favorable prognostic factor, independent of smoking status.…”
Section: Figmentioning
confidence: 96%
“…Hsu et al 78) reported that median survival was the same for never-smoking women and never-smoking men with adenocarcinoma, suggesting that both smoking status and histologic type rather than gender decided survival. In several studies, 34,40,70) a significant survival advantage for women disappeared after statistically adjusting for smoking status, although in other studies 28,41,49,51,53,57,58,76,77) survival advantages for women persisted after adjustment for smoking. In our meta-analysis, which combined these conflicting studies, female gender still persisted as a favorable prognostic factor, independent of smoking status.…”
Section: Figmentioning
confidence: 96%
“…The mechanism of cystic airspace formation in lung cancer is not fully understood. Some researchers believe that cystic airspace is correlated with rapid tumor growth that oversteps the blood supply of the tumor, thus creating necrosis in the middle of the tumor ( 22 ). Clinically, cystic airspace has been reported to be an independent factor for poor prognosis in patients with resected early-staged lung cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] The literature about the prognosis of cavitary NSCLC (NSCLC-c) compared with noncavitary NSCLC (NSCLC-nc) is limited to a few reports. The presence of the cavity in primary lung cancer has been associated with a worse prognosis in some reports based on radiographic exams and CT.[ 11 12 13 ] In other reports, however, there was no difference between cavitary lung cancer and noncavitary lung cancer. [ 14 15 ]…”
mentioning
confidence: 94%